The Impact of Industrialization on Deviant Behavior Among Adolescents - Nenden Aryanti (FISIP UIN SGD Bandung, 2021)
This research is motivated by problems that occur in society caused by industrialization. Industrialization will change the condition that the people in Rancaekek District were an agrarian society to become an industrial society. The theory used in this research is that social change occurs because of changes in elements that maintain the balance of community, such as geographical, biological, economic, or cultural elements. The research method used in this study used a qualitative method and data collection using observation and interviews. The results of this study show that before industrialization, Rancaekek Sub-district was an agricultural area. At the same time, the behavior of adolescents before and after industrial development did not experience such a big change. The impact of industrialization on adolescent deviant behavior becomes hedonism and consumptive, thereby triggering deviant behavior.